Solid Phase PEGylation of Uricase. (2017) - Nanda, Pooja; Jagadeesh Babu, P.E.
Abstract: Uricase is used as a therapeutic enzyme to treat gout and hyperuricemia which also finds application in cancer chemotherapy. Site-specific PEGylation of uricase using methoxy polyethylene glycol maleimide (mPEG-mal) through thiol PEGylation reaction is an effective way to overcome the demerit of its short plasma half-life in blood as well as for the enhancement of its therapeutic potential. However, conventional solution-phase PEGylation for the synthesis of conjugates leads to lower yields of the desired PEGylated product and thus falls short of commercial attraction. In order to preserve the bioactivity of PEGylated product, selectivity, and extent of covalent conjugation, a methodology for on-column/solid phase PEGylation of uricase enzyme using size-exclusion reaction chromatography (SERC) has been attempted. Sephadex G-100 was used as a chromatographic solid media, wherein synthesis of mono and di-PEGylated uricase molecules was observed which were efficiently separated from their non-PEGylated counterparts.